MANAJEMEN STRATEGIK KEPALA SEKOLAH DALAM IMPLEMENTASI GERAKAN TRANSISI PAUD KE SD DI KOTA SAMARINDA - Chelda Yuliana; ⁠ Muhammad Amir Masruhim; Azainil, Azainil; Susilo, Susilo; Hasbi Sjamsir; ⁠ Widyatmike Gede Mulawarman; Masrur Yahya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transition from Early Childhood Education (ECE) to Primary School is a critical phase that requires strategic school management to ensure that children's adaptation takes place in a safe, enjoyable, and developmentally appropriate environment. This study aims to analyze principals' strategic management in implementing the ECE-to-Primary School Transition Movement in Samarinda City, Indonesia. This study employed a qualitative approach with a multisite study design involving SDN 007 Samarinda Ulu, SD Muhammadiyah 2 Samarinda, and SDN 008 Samarinda Seberang. Data were collected through interviews, observations, and documentation involving school principals, Grade 1 teachers, and parents. Data credibility was established through source and technique triangulation, while the data were analyzed thematically and comparatively across the three sites. The findings indicate that principals' strategic management encompasses five major dimensions: planning, organizing, implementation, controlling, and addressing implementation barriers. These strategies include analyzing school conditions, establishing goals, developing resources, forming transition teams, communicating with parents, implementing school orientation activities, conducting initial assessments, applying enjoyable learning approaches, monitoring children's development, and undertaking evaluation and follow-up actions. The study identifies four main characteristics of strategic management in the ECE-to-primary transition: contextual, collaborative, child-centered, and adaptive. These findings emphasize that successful transition depends not only on children's readiness but also on schools' and principals' capacity to establish responsive transition systems that address children's needs and actively engage key stakeholders.